Situações vivenciadas por cuidadores familiares de idosos na atenção domiciliar - Matheus Souza Silva; Margrid Beuter; Eliane Raquel Rieth Benetti; Jamile Lais Bruinsma; Liamar Donati; Nara Marilene Oliveira Girardon-Perlini (Universidade Federal de Santa Maria, 2019)
To identify positive and negative situations experienced by family caregivers of elderly people assisted in a Home Care Service. Method: qualitative study, with data collection from march to may 2015, carried out through a sociodemographic form and semi-structured interview, submitted to the analysis of thematic content and organized into two categories, according to the Critical Incident Technique. Results: eight caregivers participated. Negative situations include prior inexperience and unawareness of technologies used for care; being alone for the care and psychophysiological changes of the caregiver. The positive situations synthesize the comfort of being at home, support from the Home Care Service and reduction in expenses with travel to health service. Conclusion: knowing the situations, positive and negative, experienced by family caregivers subsidizes the planning of actions by the health team, aiming at strengthening potentialities, reducing the difficulties of caregivers and qualifying home care.